Lesson Learned Student Entrepreneurship Activities to Increase Graduates as Entrepreneurs - Evayani, Evayani; Yacob, Noor Azuddin; Bustami, Nurshahira Binti; Hardika, Muhammad Zaki; Sabila, Afdhal; Humaira, Malika; W. Sebayang, Ardhi; Lia, Karesya Audi; Hilmiy, Muhammad Dzaki; Arafat, Muhammad Fathin; Hafidhillah, Muhammad; Faziya, Siti Raisha; Dellia, Adisti (Asian Journal of Community Services, 2023)
Lesson learned, aimed to provide students with entrepreneurial experiences and give the skill for entrepreneurship. The approach that can be employed is to integrate entrepreneurial activities into the curriculum and extra curriculum. The method used is sharing sessions. The activity held in UKM, attended by 67 students. The results indicated that factors to be considered in becoming an entrepreneur include education, soft skills, support, mentorship, creativity, innovation, and a strong passion. The lessons learned from successful entrepreneur alumni showed that entrepreneurial education provided by experienced entrepreneurs can have a positive impact on students' attitudes and motivation towards entrepreneurship. Future suggestion initiatives should attend other stake holder to sharing their experiences, such as government, creditor, and investor.